Open Source Seed, a Revolution in Breeding or Yet Another Attack on the Breeder’s Exemption? - Louwaars, Niels (Frontiers in Plant Science, 2019)
The Open Source Seed Initiative was initiated in 2012. Following concerns about the concentration in the seed sector and the rise of patenting, the initiative is “dedicated to maintaining fair and open access to plant genetic resources worldwide in order to ensure the availability of germplasm to farmers, gardeners, breeders, and communities of this and future generations.” Inspired by the debate on the anti-commons and the open source software movement, the initiative wants to create a viral system to “free” genetic resources: the use of “freed” genetic resources is made conditional to any materials derived from them being made available under the same “open source” conditions. This would be achieved under a “pledge” (in the USA) or a license contract (in Germany). The objective of this paper is to analyze whether these open source seed initiatives may deliver their goals. We compare the concept with the open innovation character of the plant breeder’s rights system, exemplified by the breeder’s exemption, and the major other open source initiative in the sector, BiOS. We also present other ways to limit negative impact of the patent system on plant breeding. We conclude that national sovereign rights on genetic resources may challenge the open source goals and that the German initiative may contribute to legal complexities in the seed sector. The open source movement may even contribute to the trend that openness (through the breeder’s exemption) is challenged despite the intentions to the contrary. In fact, the initiatives not only free the genetic resource but also treat seeds as a common good. We question the sustainability of the business models for that approach and thus the societal benefits that can be expected from plant breeding, which may illustrate the tragedy of the commons.